BN manifesto to reduce cost of living can be achieved - Lecturer - Borneo Post, (KK) (Borneo Post (KK), 2013)
KUALA LUMPUR: The Barisan Nasional (BN) manifesto to reduce the people's cost of living is seen as more realistic and can be achieved in five years, said Prof Amir Hussin Baharuddin of Universiti Utara Malaysia (UUM).